(untitled) (Dhaka University Journal of Biological Sciences, 2023)
Chrysanthemum morifolium is one of the most famous cut flowers with a high ornamental value, occupying an irreplaceable position in international flower commerce. But most frequently occurred fungal diseases limit the production of this ornamental plant. A total of five fungicides viz., CM-75 WP, Dithane M 45, Ridomil Gold MZ 68 WG, Rovral 50 WP and Score 250 EC were selected to evaluate in vitro efficacy at 100, 200, 300, 400 and 500 ppm concentrations against two pathogenic fungi of Chrysanthemum morifolium namely, Curvularia lunata and Fusarium moniliforme. Rovral 50 WP showed complete growth inhibition of C. lunata and CM 75 WP showed complete growth inhibition of F. moniliforme at all concentrations used. Five plant extracts viz., Azadirachta indica, Citrus limon, Datura metel, Psidium guajava and Vitex negundo were selected to evaluate in vitro efficacy at 5, 10, 15 and 20% concentrations against the test pathogens. Out of the five plant extracts, A. indica showed complete growth inhibition of C. lunata at 15 and 20% concentrations. On the other hand, P. guajava showed complete growth inhibition of F. moniliforme at 20% concentrations. Dhaka Univ. J. Biol. Sci. 31(2): 281-288, 2022 (July)